The relationship between early feeding skills and general movements of preterm infants in the neonatal intensive care unit - Ayaz Taş, Seda; Yakıt Yeşilyurt, Seda; Birinci Olgun, Tansu; Tezcan, Sezen; Taş, Sinan; Dilek, Mustafa (The Turkish Journal of Pediatrics, 2026)
Background. Early feeding skills and general movements (GMs) are negatively affected by hypotonia due to prematurity. Interventions for feeding skills can be guided by understanding the relationship between feeding skills and GMs. In the light of this, the study focused on understanding the relationship between early feeding skills and preterm infants’ GMs in the neonatal intensive care unit (NICU). Methods. Participants in this cross-sectional study were forty infants with a postmenstrual age of 34–37 weeks who were hospitalized in the NICU at Abant İzzet Baysal University Training and Research Hospital. The data consisted of demographic characteristics (birth weight, gestational age, date of birth, age, and sex), feeding skills, assessed with the Early Feeding Skills Assessment Tool, and GMs, assessed with the General Movement Assessment. Results. A strong correlation was found between the Oral-Motor Function subscale of the Early Feeding Skills Assessment Tool and the Upper Limbs subscale of the General Movements Motor Optimality Score (rho=0.74, p=0.001). Among the demographic characteristics, only maternal age was associated with feeding skills. A weak correlation was determined between the Physiologic Stability subscale of the Early Feeding Skills Assessment Tool and maternal age (rho=0.34 p=0.03). Conclusions. This study reveals the relationship between feeding skills and general movement of preterm infants at NICU. GMs of upper extremity were found to positively affect feeding skills. This process may be accelerated by interventions to improve the GMs of upper extremity during the transition to oral feeding.